Implementasi Budaya 5S dalam Membangun karakter Religius Siswa di MI Miftahul Akhlaqiyah - Kalimatus Sadiyah (HAWARI : Jurnal Pendidikan Agama dan Keagamaan Islam, 2025)
Lack of manners can affect a student’s personality. This research aims to find out how the 5S culture is implemented in shaping the character of students at MI Miftahul Akhlaqiyah. The method used in this research is qualitative with data collection through observation, interviews and documentation. The research results show that the implementation of 5S culture in this school has gone well. Every morning, students are greeted by the picket teacher and taught to say hello and smile. Teachers also provide role models and advice on maintaining good manners and continuously monitoring student behavior. The 5S culture at MI Miftahul Akhlaqiyah involves various methods, including habituation, advice, example and supervision. The main supporting factor is cooperation between school principals and teachers in providing good examples. However, there are also several challenges, such as students who sometimes forget to apply 5S and the influence of the external environment, such as friends and technology, which can affect students’ character. However, it is hoped that consistent implementation of the 5S culture can help build students’ better religious character, teach them to respect each other, and create a harmonious atmosphere at school.